Germany and Namibia as co-leads for the United Nations: Chances and challenges on the road to the 2024 UN Summit of the future - Marianne Beisheim; Silke Weinlich (Stiftung Wissenschaft und Politik (SWP), 2023)
The President of the United Nations General Assembly has appointed the German and Namibian permanent representatives as co-facilitators for the Summit of the Future. The summit is scheduled for September 2024. Its aim is to reinforce the UN and global governance structures to better address old and new challenges. That includes making progress on implementing the sustainable development goals (SDGs) by 2030. Given the current geopolitical tensions, this will be no easy task. At this juncture it is important to get the process off to a good start in order to gather support, generate attention and engender confidence.
Keywords: 320; Germany; Namibia; United Nations; 2024 UN Summit of the Future; sustainable development goals (SDGs); António Guterres